2020
DOI: 10.3390/s20071810
|View full text |Cite
|
Sign up to set email alerts
|

Presentation Attack Face Image Generation Based on a Deep Generative Adversarial Network

Abstract: Although face-based biometric recognition systems have been widely used in many applications, this type of recognition method is still vulnerable to presentation attacks, which use fake samples to deceive the recognition system. To overcome this problem, presentation attack detection (PAD) methods for face recognition systems (face-PAD), which aim to classify real and presentation attack face images before performing a recognition task, have been developed. However, the performance of PAD systems is limited an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…Recently, with the development of learning-based techniques, deep learning has been widely used in computer vision research. This technique has been successfully applied to various computer vision/pattern recognition problems such as image classification [ 23 , 24 , 25 , 26 , 27 ], object detection [ 32 , 33 ], and image generation [ 34 , 35 , 36 ]. The success of deep learning comes from the fact that this technique simulates the way in which the human brain processes information (images).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Recently, with the development of learning-based techniques, deep learning has been widely used in computer vision research. This technique has been successfully applied to various computer vision/pattern recognition problems such as image classification [ 23 , 24 , 25 , 26 , 27 ], object detection [ 32 , 33 ], and image generation [ 34 , 35 , 36 ]. The success of deep learning comes from the fact that this technique simulates the way in which the human brain processes information (images).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Zhu et al [27] proposed CycleGAN, which translates images from the source domain to the target domain with the cycle consistency loss, and this method shows remarkable results in the style transfer task. Researchers have extended unpaired image-to-image translation for several applications [51][52][53][54][55][56][57][58] to address issues such as data imbalance, lack of diversity, and limitation in collecting real paired dataset.…”
Section: Image-to-image Translationmentioning
confidence: 99%
“…To prepare for such a presentation attack detection (PAD), Nguyen et al [55] generalized the model to fake presentation attack face images obtained via CycleGAN. Inspired by these studies, we employed the image-to-image translation to refine the localization mask using pseudo-line data, and the effectiveness of a refinement network is shown in an ablation study later on.…”
Section: Image-to-image Translationmentioning
confidence: 99%
“…However, a large body of research has demonstrated the vulnerability of face recognition systems against presentation attacks, where an adversary attempts to subvert a recognition system by presenting a facial artefact, which mimics facial biometric features of a legitimate user [8,24,27,28]. Based on the artefact used, typical 2D facial presentation attacks involve three categories: printed photo attacks, electronic facial image attacks, and facial video attacks [7,11,17,19,33].…”
Section: Introductionmentioning
confidence: 99%